1974
DOI: 10.1139/v74-328
|View full text |Cite
|
Sign up to set email alerts
|

Virial Partitioning of Charge Distributions and Properties of Diatomic Hydrides; NaH ↔ HCl

Abstract: . Can. J. Chem. 52, 2268Chem. 52, (1974 The virial partitioning method is applied to the ground states of the AH diatomic hydrides (A = Na, Mg, Al, Si, P, S, C1) in their neutral and charged forms. This is a spatial partitioning of a molecular system, the partitioning surfaces, which in this instance divide each molecule into an (A) and an (H) fragment, bcing determined by the topographical features of the electronic charge distribution. The kinetic and potential energies of the virial fragments are well-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Other methods for estimating atomic charges applied to boron clusters and similar species include the refinement of electron populations in density basis sets and radial integration of the total density out to a fixed radius or surface (Ito & Higashi, 1983;Bader & Messer, 1974). The former technique provides information relevant to postulated sets of orbitals but frequently overestimates atomic charges.…”
Section: A2(q) = (4nr 3/v)2 × ~{[Sin(rs) -Rscos(rs)]2/(rs)6}a2(f)mentioning
confidence: 99%
“…Other methods for estimating atomic charges applied to boron clusters and similar species include the refinement of electron populations in density basis sets and radial integration of the total density out to a fixed radius or surface (Ito & Higashi, 1983;Bader & Messer, 1974). The former technique provides information relevant to postulated sets of orbitals but frequently overestimates atomic charges.…”
Section: A2(q) = (4nr 3/v)2 × ~{[Sin(rs) -Rscos(rs)]2/(rs)6}a2(f)mentioning
confidence: 99%
“…The first is due to Bader and coworkers (Bader andBeddall 1972, 1973;Bader and Messer 1974) and the second to Hirshfeld (1977). We briefly describe each of these schemes and then compare the charges derived from near Hartree-Fock limit diatomic wavefunctions by both schemes.…”
Section: Desiderata For Charge Partitioningmentioning
confidence: 99%
“…ionicity and acidity), as is evident from the analyses of diatomic molecules by , , Bader and Messer (1974), and of aliphatic alcohols and amines by Stutchbury and Cooper (1983). The fact that typical electron populations for the fragments are usually quite different from those of neutral atoms has received limited attention so far.…”
Section: Bader Partitioningmentioning
confidence: 99%
“…This is the boundary condition necessary for application of Schwinger's principle of stationary action to an open system [49]. An extensive body of work [16][17][18][19][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] has revealed that virial partitioning gives a natural and rigorous meaning to the intuitive concept of an atom in a molecule, and convergence of the electrostatic interaction based on topological atoms has been computationally demonstrated [64][65][66]. An extensive body of work [16][17][18][19][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] has revealed that virial partitioning gives a natural and rigorous meaning to the intuitive concept of an atom in a molecule, and convergence of the electrostatic interaction based on topological atoms has been computationally demonstrated [64][65][66].…”
Section: Electron Density As the Basic Variablementioning
confidence: 99%